1987
DOI: 10.1136/bmj.295.6602.807
|View full text |Cite
|
Sign up to set email alerts
|

The changing pattern of alcohol consumption in England and Wales 1978-85.

Abstract: Overall alcohol consumption remained virtually unchanged. Men showed little difference in drinking habits, except for the 18-24 age group, who seemed to be drinking less. For women mean alcohol consumption in 1985 was similar to that in 1978, but more women were not drinking at all so the mean alcohol consumption per drinker had risen. As with earlier work, this study showed that social class had little influence on alcohol consumption, while being married seemed to have a moderating effect. A variable regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…Further reassurance on the validity of the present data may be found in the frequency of reporting the use of different benzodiazepines (Dunbar et al, 1987). When placed in rank order and compared with prescription data obtained from the DHSS, a Spearman rank correlation coefficient of 0.903 was obtained (/)=0.002).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Further reassurance on the validity of the present data may be found in the frequency of reporting the use of different benzodiazepines (Dunbar et al, 1987). When placed in rank order and compared with prescription data obtained from the DHSS, a Spearman rank correlation coefficient of 0.903 was obtained (/)=0.002).…”
Section: Discussionsupporting
confidence: 54%
“…Problems of estimating alcohol consumption were discussed by Wilson (1981). Comparisons of Customs & Excise figures with alcohol consumption reported in the present survey (Dunbar & Morgan, 1987) showed somewhat less under-reporting than in a comparable study by Wilson (1980). However, reported consumption represented only 58% of actual consumption as detailed by H.M. Customs & Excise.…”
Section: Discussionsupporting
confidence: 42%
“…This pattern has also been reported for Spain by social class in men9 and by educational level in men and women 48. However, other studies have found no association between alcohol consumption and social class49or have found an association showing that people of higher social class drink more 50. One study in the north of Europe has detected a change in the excessive alcohol consumption by social class: in the 1960s or 1970s non-manual workers drank more, a pattern that reversed during the 1980s 51.…”
Section: Discussionmentioning
confidence: 98%
“…As sexually immature rats may not have a direct clinical equivalent, studies were also carried out in sexually mature, more slowly growing, rats. It is noteworthy that recent published data have shown that increasing numbers of teenagers regularly drink ethanol in quantities considered to be clinically prohibitive [7]. However, as the sexually immature rats were mature at the end of the feeding regime, we have also distinguished between both sets of animals by the terms 'small' and 'large' respectively.…”
Section: L-[4-3h]phenylalanine Was Obtained From Amershammentioning
confidence: 98%